A revision of European species of the genera Melanagromyza Hendel and Hexomyza Enderlein, with a supplement on the genus Ophiomyia Braschnikov (Diptera: Agromyzidae). - Spencer, Kenneth Angus (Contributions to Entomology = Beiträge zur Entomologie, 1966)
All Palaearctic species described in or subsequently transferred to the genus Melanagromyza Hendel have been examined. On the basis of this study the generic concept of Melanagromyza has been restricted and the genus Hexomyza Enderlein is revived witli amended concepts. Twenty-five species are now included in Melanagromyza, including four new species, and for these an entirely new key is given. Four gall-causing species are included in Hexomyza. In a Supplement to the author’s recent (1964) Revision of Ophiomyia species three new species are described, four further species are transferred to Ophiomyia from Melanagromyza and three new synonomies are established. Illustrations are given of the male genitalia of all but two species, of which only the female is known. Nomenclatural Acts squamata Becker, 1903 (Agromyza), syn. n. of Melanagromyza sojae (Zehntner, 1900) salicis (Malloch, 1913) (Hexomyza), comb. n. hitherto Agromyza salicis schineri (Giraud, 1861) (Hexomyza), Lectotype; comb. n. hitherto Agromyza schineri simplicoides (Hendel, 1920) (Hexomyza), Lectotype; comb. n. hitherto Melanagromyza simplicoides aenea (Meigen, 1830) (Melanagromyza), Lectotype described as Agromyza aenea albocilia Hendel, 1931 (Melanagromyza), Lectotype cecidogena Hering, 1927 (Melanagromyza), syn. n. of Hexomyza salicis (Malloch, 1913) cunctans (Meigen, 1830) (Melanagromyza), Lectotype described as Agromyza cunctans euphorbiae Hendel, 1923 (Melanagromyza), syn. n. of Ophiomyia beckeri (Hendel, 1923) ferulae (Spencer, 1966) (Melanagromyza), spec. n. goniaea Hendel, 1931 (Melanagromyza), syn. n. of Ophiomyia beckeri (Hendel, 1923) knautiae Hering, 1944 (Melanagromyza), syn. n. of Ophiomyia longilingua (Hendel, 1920) multiseta Rydén, 1949 (Melanagromyza), syn. n. of Melanagromyza lappae (Loew, 1850) nitens Rohdendorf-Holmanová, 1958 (Melanagromyza), syn. n. of Melanagromyza lappae (Loew, 1850) paracelsus Hering, 1933 (Melanagromyza), syn. n. of Ophiomyia orbiculata (Hendel, 1931) rohdendorfi Spencer, 1966 (Melanagromyza), spec. n. siciliensis Spencer, 1966 (Melanagromyza), spec. n. submetallescens Spencer, 1966 (Melanagromyza), spec. n. fuscociliata Hendel, 1931 (Melanagromyza aeneiventris), syn. n. of Melanagromyza aenea (Meigen, 1830) dianellae (Kleinschmidt, 1961) (Ophiomyia), comb. n. hitherto Melanagromyza dianellae improvisa Spencer, 1966 (Ophiomyia), spec. n. inaequabilis (Hendel, 1931) (Ophiomyia), Lectotype; comb. n. hitherto Melanagromyza inaequabilis longilingua (Hendel, 1920) (Ophiomyia), Lectotype; comb. n. hitherto Melanagromyza longilingua ononidis Spencer, 1966 (Ophiomyia), spec. n. paramonovi Spencer, 1963 (Ophiomyia), comb. n. hitherto Melanagromyza paramonovi rostrata (Hendel, 1920) (Ophiomyia), Lectotype; comb. n. hitherto Melanagromyza rostrata simplex (Loew, 1869) (Ophiomyia), comb. n. hitherto Agromyza simplex suavis Spencer, 1966 (Ophiomyia), spec. n.